2014
DOI: 10.1007/s10585-014-9677-y
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ can stimulate the p38/β-catenin/PPARγ signaling pathway to promote the EMT, invasion and migration of non-small cell lung cancer (H460 cells)

Abstract: Signaling pathway(s) responsible for transforming growth factor β (TGFβ)-induced epithelial mesenchymal transition (EMT), invasion and migration of H460 cells (non-small cell lung cancer/NSCLC) was identified in the study. The results showed that TGFβ-induced p(38)/β-catenin/PPARγ signaling pathway played a critical role in the promotion of EMT, invasion and migration of H460 cells. All these pathological outcomes attributed to PPARγ-increased expression of p-EGFR, p-c-MET and Vimentin and the decrease of E-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Tumor budding was characterized by increased expression for both β -catenin and p16 (cyclin-dependent kinase inhibitor 2A) [68]. β -Catenin is important for linkage of E-cadherins to the cytoskeleton [80, 81]. The downregulation of E-cadherin in carcinoma cells is associated with increased invasive ability of cancer cells [82, 83].…”
Section: Wnt/β-catenin Signal Pathway In Tumor Buddingmentioning
confidence: 99%
“…Tumor budding was characterized by increased expression for both β -catenin and p16 (cyclin-dependent kinase inhibitor 2A) [68]. β -Catenin is important for linkage of E-cadherins to the cytoskeleton [80, 81]. The downregulation of E-cadherin in carcinoma cells is associated with increased invasive ability of cancer cells [82, 83].…”
Section: Wnt/β-catenin Signal Pathway In Tumor Buddingmentioning
confidence: 99%
“…Recent studies have identified several signaling pathways for TGF-β-induced EMT [22]. In particular, the TGF-β/p38 mitogen-activated protein kinase (MAPK) signaling pathway is a well-investigated inducer of EMT in a variety of cancers, including lung cancer, renal cancer, breast cancer, and liver cancer [26-29]. …”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that another study reported that TGFb suppresses b-catenin/Wnt signaling and enhances cell adhesion in CRC in a Smad4-independent manner [132]. A similar study to that of Demangy et al, reported the ability of TGFb to promote the EMT and invasion in a p38 MAPK/b-catenin/peroxisome proliferator-activated receptor g-dependent manner in non-small cell lung cancers [137].…”
Section: Wnt Signaling Cascadementioning
confidence: 63%